2013
DOI: 10.1186/1746-1596-8-138
|View full text |Cite
|
Sign up to set email alerts
|

CyclinD1, a prominent prognostic marker for endometrial diseases

Abstract: PurposeAlteration of CyclinD1 was suggested to relate with development of endometrial carcinogenesis before, however CyclinD1 expression is not well defined in endometrial hyperplasia lesions. We checked the relationship between its expression and clinic-pathological variables of endometrial lesions to explore the possibility for CyclinD1 as a potential diagnostic and prognostic marker.MethodsCyclin D1 immunohistochemical analysis (IHC) was used to evaluate 201 fixed, paraffin-embedded endometrial samples whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 20 publications
6
51
4
1
Order By: Relevance
“…In the present study, we demonstrated that the cyclin D1 LI was consistently higher than the Ki-67 LI. Cyclin D1 is associated with oncogenesis of various types of tumors, including mantle cell lymphoma [24], breast cancer [25], esophageal carcinoma [26], endometrioid carcinoma [27], gastric carcinoma [28], bladder cancer [29], and cholesteatoma [30]. In brain tumors, the expression of cyclin D1 has been reported in medulloblastomas [31].…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we demonstrated that the cyclin D1 LI was consistently higher than the Ki-67 LI. Cyclin D1 is associated with oncogenesis of various types of tumors, including mantle cell lymphoma [24], breast cancer [25], esophageal carcinoma [26], endometrioid carcinoma [27], gastric carcinoma [28], bladder cancer [29], and cholesteatoma [30]. In brain tumors, the expression of cyclin D1 has been reported in medulloblastomas [31].…”
Section: Discussionmentioning
confidence: 98%
“…Studies in colorectal cancer have confirmed that downregulation of MAGL leads to decreased expression of Cyclin D1 and Bcl‐2, thereby inhibiting the proliferation of colorectal cancer and promoting tumor apoptosis or/and cell cycle arrest . Cyclin D1, the protein encoded by CCND1, plays an important and positive role during the key rate‐limiting point, the G1 → S phase transition, in the cell cycle, and Bcl‐2 is an antagonistic protein in the process of apoptosis or programmed death and is thought to prolong the survival of cells in tumors. In our study, we used the same experimental scheme to confirm whether MAGL inhibition MAGL resulted in a reduction in Cyclin D1 and Bcl‐2 in EC, which would lead to impairment of tumor pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that cyclin D1 is implicated in the cell cycle progression of various tumors and is associated with the cell proliferative activity and differentiation of OC. Suppression of cyclin D1 is closely correlated with reduced tumorigenicity [16,17]. In this study, we examined the protein expression of c-myc and cyclin D1 by western blot analysis after PRR11 overexpression.…”
Section: Discussionmentioning
confidence: 99%